Study of progesterone level during first trimester of pregnancy in cows. - Jawad K. Taher; Khawla A. Hussein (University of Thi-Qar Journal of agricultural research, 2022)
Measurement of progesterone is an indirect method for pregnancy diagnosis in many livestock species including cattle, buffaloes, sheep, and goats. Conception extends the life of the corpus luteum (CL) by preventing the luteolytic mechanism from being triggered, thus prolonging and maintaining its functional characteristics, ensuring continued high progesterone levels (Spencer, et.al., 1995). (Shemesh et al., 1973) proposed that the difference in peripheral plasma progesterone levels between pregnant and non pregnant cows, 19 days after insemination, can form the basis for a very early pregnancy test. (Laing and Heap 1972) first documented this in milk to diagnose cows in early pregnancy Progesterone maintains the uterine endometrium in a state which supports embryonic development, implantation, and foetoplacental development. Progesterone concentrations vary with the stage of the estrous cycle which makes it one of the most commonly studied reproductive hormones in bovine ruminants for pregnancy detection and ovarian activity (Kaneko,et.al.,1994). Studies in the bovine estrous cycle indicate that the milk or serum progesterone concentrations reach a maximum value 13-14 days after estrus, and if the animal is pregnant, these continue to remain elevated up to day 21 after fertilization (Parkinson, et al.,1994) . These high levels of progesterone in serum or milk between days 18 and 24 after insemination form the basis of establishment of pregnancy in cattle (Sasser, and Ruder,1987; Shemesh,1973). Interferon-???? exerts its antiluteolytic effect by inhibiting the endometrial expression of oxytocin receptors, through which oxytocin stimulates pulsatile PGF2???? release (Wolf,2003). Although low progesterone concentrations at 18 to 24 days after breeding can accurately predict non pregnancy, high progesterone concentrations during this period are not the specific indicators of pregnancy due to variations among cows in duration of the estrous cycle as well as the incidence of early or late embryonic mortality. The advantages of progesterone assay for pregnancy diagnosis include noninvasive collection of milk sample and the feasibility to conduct the test on the farm using commercial cow-side milk progesterone test kits [Pennington,1985 ; Gowan,1982 ; Wimpy,et.al.,1986), though the sensitivity gets compromised to some extent with these assay kits. Key Word: progesterone, pregnancy, cows